Optimasi Durasi Fiksasi Alkohol 96% sebagai Upaya Peningkatan Kualitas Pap Smear pada Fasilitas Kesehatan dengan Sumber Daya Terbatas - Nurhilaliyah Nurhilaliyah; Wiwin Marsenda; Ka'bah Ka'bah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Cervical cancer requires early detection through Pap smear cytology, but its diagnostic accuracy in health facilities with limited resources is often hampered by the variability of preparation quality due to fixation. This study aims to optimize the duration of 96% alcohol fixation on the quality of Pap smear preparations as a basis for developing standard operating procedures (SOPs). The study used a repeated measures experimental design on eight tightly controlled samples to minimize confounding variables, resulting in 24 observations with varying durations of 5, 15, and 30 minutes. Preparation quality was objectively assessed using a structured scoring system based on modified Bethesda criteria that include nuclear morphology, cytoplasmic characteristics, and background clarity. The results showed a statistically significant difference (Friedman test, p = 0.001). A duration of 30 minutes consistently provided optimal results across all samples. Although this is a preliminary study with a limited number of samples, consistent results in the repeated measures design indicate a duration of 30 minutes as the most ideal fixation condition to maintain cell integrity. These findings provide an empirical basis for resource-constrained laboratories to standardize fixation procedures to improve diagnostic accuracy.